Factors affecting pregnant women conducting ANC (Antenatal Care) visits at the Rambung Tebing Tinggi health center in 2023 - Sari, Maya; Saragih, Rapida (Sean Institute, 2024)
The low coverage of K1 and K4 in pregnant women is caused by several factors. The gap between K1 and K4 in 2022 is around 6%. And there was a decrease in visits at the beginning of 2023, precisely in semester I january to june, it was found that 21 people did not carry out their pregnancy check visits from 89 pregnant women. This shows that the percentage of K1 coverage of 76.40% and K4 of 77.5% at the Rambung Health Center is still far from the target set based on the Minimum Service Standard (SPM) of 95%. The purpose of the study was to analyze the factors (education, parity and mileage) that affect pregnant women carrying out ANC visits in the working area of the Rambung Health Center in Tebing Tinggi City in 2023. This study uses a quantitative research type, with a descriptive correlational design. The design of this study used a cross sectional design. The population in this study were all pregnant women who made a pregnancy visit at the Rambung Health Center in Tebing Tinggi City in 2023, the sampling technique used was purposive sampling, a sample of 35 people was obtained. This study was analyzed bivariate with Chi-Square statistical test. The results of this study there is a relationship between the level of education of pregnant women about ANC with ANC visits (p value = 0.0001), there is a relationship between parity and ANC visits (p = 0.012), there is a relationship between the distance from home of pregnant women and ANC visits (p value = 0.007) in Tebing Tinggi City Rambung Health Center in 2023. In conclusion, there is an influence of education, parity and distance with the completeness of ANC (antenatal care) visits for pregnant women at the Rambung Health Center in Tebing Tinggi City in 2023 In conclusion, there is an influence of education with the completeness of ANC (antenatal care) visits, there is an influence of parity with the completeness of ANC (antenatal care) visits and there is an influence of mileage with the completeness of ANC (antenatal care) visits for pregnant women at the Rambung Health Center in Tebing Tinggi City in 2023